THE ROLE OF TEACHER’S GESTURE AND VOICE TONE IN THE TEACHING PROCESS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Effective teaching is not only about what is taught but also how it is communicated. Gestures and voice tone are crucial tools in a teacher’s communicative arsenal that contribute significantly to classroom dynamics and student learning. These nonverbal cues support meaning-making, sustain attention, and bridge gaps in understanding, particularly for complex or abstract content. This paper investigates the functions and benefits of gestures and vocal modulation in teaching, backed by evidence from cognitive psychology, pedagogy, and communication theory. By analyzing empirical studies and theoretical models, we show that these expressive modalities improve comprehension, emotional engagement, and memory retention. The paper concludes with recommendations for integrating these tools into teacher training and pedagogical design.